Prediction of Archetype Personality on Competence and Entrepreneurial Success: Phase-By-Phase Analysis - Wikantiyoso, Bimo (AIBPM Publisher, 2024)
This study aims to present a conceptual model and provide empirical evidence regarding entrepreneurial archetype and competence in influencing entrepreneurial success, particularly in Small and Medium Enterprises (SMEs). Previous research has found that individual factors such as personality and competence play a significant role in business success. However, the literature on entrepreneurial personality lacks discussion on the role of archetypes in business success. The archetype approach attempts to explain the basic patterns of personal dynamics in self-resource management and environmental interaction. This study uses the Hero's Journey archetype to explain the entrepreneurial journey, comprising 12 archetypes divided into three phases: initiation, journey, and return. The entrepreneurial competence approach by Spencer & Spencer, explaining 13 capabilities, and the business success concept by Kaplan & Norton, addressing financial, internal business processes, and employee satisfaction, are used. The study involves 500 entrepreneurs in Java using Structural Equation Modelling (SEM). The results show that each phase of the archetype journey significantly affects entrepreneurial competence and success. This study offers a new understanding of entrepreneurial personality using the archetype approach, highlighting its importance in enhancing business success.